A Roadmap Of Customers Perception Towards Mutual Funds In Uttar Pradesh With Special Reference To Lucknow City (International Journal of Scientific Research and Management (IJSRM), 2017)
The mutual fund investment has gained momentum in the last few years. The aspects of mutual funds are huge as the schemes of investment are numerous. The article is all about finding the perception and the awareness level among the customers in terms of mutual funds. The perception level of the customers has been found by analyzing the data with the help of SPSS. The end findings which could be extracted from the analysis were that the mutual fund is a tax saving investment and to a certain extent a return oriented investment. The other finding which was found out that the investors were more prone to public companies rather than the private companies.